Levels of Estrogen Receptors α and β in Frontal Cortex of Patients with Alzheimer's Disease: Relationship to Mini-Mental State Examination Scores - Kelly, Jeremiah F.; Bienias, Julia L.; Shah, Avni; Meeke, Kathleen A.; Schneider, Julie A.; Soriano, Edwin; Bennett, David A. (Current Alzheimer Research, 2008)
Estrogen exerts beneficial effects on the brain throughout life. Studies demonstrate that estrogen is neuroprotective and that reduced brain estrogen activity may influence the clinical course of Alzheimer's disease (AD). Changes in levels of estrogen receptors have been detected in postmortem brain tissue of AD patients. Very little is known about the relationship between clinical stage and levels of estrogen receptors in postmortem brain. We hypothesized that estrogen receptor levels would be related to severity of cognitive impairment assessed proximate to death. Western blotting was used to quantify ER-α and ER-β in nuclear, cytosolic, and crude membrane fractions of superior frontal cortex from 25 AD patients. Multiple linear regression analyses adjusted for age, sex, and education showed a significant linear relationship between Mini-Mental State Examination score (MMSE) and wild-type nuclear ER-α (â = 5.463, p = 0.03), but none between MMSE and wild-type nuclear ER-β (â = 2.29, p = 0.36). We incidentally observed additional higher and lower molecular mass bands for ER-α in study subjects. Additional experiments performed on frontal cortex nuclear fractions prepared from subjects enrolled in a different study confirmed that these same bands are present in female and males with and without AD. Together our data show a relationship between wild-type ER-α and level of cognitive impairment in AD, and also suggest the possibility that variant isoforms of ER-α may be present in frontal cortex of patients with and without AD.
Keywords: dementia